Students Error In Writing Recount Text Of Twelve Grade Of Sma Negeri 2 Padangpanjang - Melisa, Venna; Syam, Erlinda (Inovasi Pendidikan, 2023)
The issues which were explained were the student’s errors in writing recount text focused on past tense and the most significant errors found in their writing recount text focused on the past tense. This research aimed to find out the student errors in writing made by the students in a text focused on past tense and the most significant errors found in writing made by the students recount text focused on the past tense. The data and source of this research were the students’ errors in writing recount text and collected on August 19, 2022. The design of the research was qualitative descriptive. This type of qualitative descriptive research is a research method that utilizes qualitative data and is described descriptively. This type of qualitative descriptive research is often used to analyze social events, phenomena or circumstances. The participants of this research were 25 students in class XII MIPA 5. The research showed that there were 179 errors found in the writing students, consisting of nine errors on omission, 18 errors on addition, 150 errors on misformation and two errors on misordering. The research results found a dominant error in misformation with a frequency of 83,79 %. It can be concluded that the students are still confused and have a problem with writing.Keyword: Error, Writing, Recount Text